2014
DOI: 10.1007/s11095-014-1542-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pluronic® P123 Formulation on the Nitric Oxide-Generating Drug JS-K

Abstract: Purpose O2-(2,4-dinitrophenyl)1-[(4-ethoxycarbonyl)piperazin-1-yl]diazen-1-ium-1,2-diolate] or JS-K is a nitric oxide-producing prodrug of the arylated diazeniumdiolate class with promising anti-tumor activity. JS-K has challenging solubility and stability properties. We aimed to characterize and compare Pluronic® P123-formulated JS-K (P123/JS-K) with free JS-K. Methods We determined micelle size, shape, and critical micelle concentration of Pluronic® P123. Efficacy was evaluated in vitro using HL-60 and U93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…12 In addition, JS-K also significantly inhibits the growth of HL-60 and OPM1 multiple myeloma cells inoculated subcutaneously in mice. 3,6,29 Therefore, JS-K exhibits significant anti-cancer activity in both solid tumours and blood malignancies. However, the role of JS-K in the treatment of orthotopic tumours is controversial because JS-K inhibited the growth of human hepatoma JM-1 cells implanted intrahepatically in nude rats 2 ; however, it did not result in tumour growth retardation or extend survival within tracranial U87 rat glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, JS-K also significantly inhibits the growth of HL-60 and OPM1 multiple myeloma cells inoculated subcutaneously in mice. 3,6,29 Therefore, JS-K exhibits significant anti-cancer activity in both solid tumours and blood malignancies. However, the role of JS-K in the treatment of orthotopic tumours is controversial because JS-K inhibited the growth of human hepatoma JM-1 cells implanted intrahepatically in nude rats 2 ; however, it did not result in tumour growth retardation or extend survival within tracranial U87 rat glioma.…”
Section: Discussionmentioning
confidence: 99%
“…In compliance with our results, JS‐K suppresses the growth of some solid tumour cells subcutaneously implanted into the flank of nude mice, including human prostate cancer (PPC‐1) and NSCLC (H1703 and H1944) cells . In addition, JS‐K also significantly inhibits the growth of HL‐60 and OPM1 multiple myeloma cells inoculated subcutaneously in mice . Therefore, JS‐K exhibits significant anti‐cancer activity in both solid tumours and blood malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…While JS-K has been shown to be advantageous in treating cancer, its clinical use has been hindered with reports of poor solubility. Structural modification of JS-K is able to prolong its half-life, and combining JS-K with special nanoparticles can greatly improve its solubility and stability, 103 , 113 further improving its prospects for clinical applications. JS-K and many other NO prodrugs represent an innovative biological approach in the development of anticancer therapeutics.…”
Section: Prodrugs Of Gstπmentioning
confidence: 99%
“…The idea for the present study originated from some recent reports on nitric oxide and its antitumor activity studies. Shami and co‐workers reported that NO has a direct cytotoxic effect on tumor cells. They mentioned that NO leads to the apoptosis of tumor cells through the posttranslational modification of several important proteins.…”
Section: Introductionmentioning
confidence: 99%